Development status of mouthguard - Biqi, Wang; Xinyu, Wang (Frontiers in Dental Medicine, 2024)
The mouthguard plays a crucial role in preventing damage to the oral and jaw system. However, the popularity of sports mouthguards remains relatively low, and research on sports mouthguards is rather scattered. This paper primarily summarizes the characteristics of materials, production methods, protection principles, and influencing factors of mouthguards, with the aim of providing a theoretical reference for the popularization and application of mouthguards.